Composto orgânico no desenvolvimento e comportamento germinativo de sementes de chia - Santos, Liliane Sabino dos. (2021)
The present work aimed to evaluate the effects caused by organic and mineral compound (NPK) on agronomic performance and physiological quality of chia seeds in the conditions of Brejo Paraibano. The experiment was conducted in the seedling nursery of the Agriculture Sector of the Federal University of Paraíba. Where the following production parameters were evaluated: plant height, number of leaves, stem diameter, number of inflorescences, submitted to different organic compound doses (250 g 500 g 700 g) and mineral fertilizer (NPK 5.46 g). For seed analysis, the variables considered were germination test (G), germination speed index (GI), mean germination time (TMG) and dry mass. The experiment was carried out in a 3.5l capacity, where it was filled to the limit with soil and revolving. The experimental design was IHD with 10 replicates and 5 treatments totaling 50 vessels. In addition, the seeds were exposed to the following osmotic potentials 0.0 -0.2, -0.4, -0.6 and -0.8 MPa, induced with NaCl along with hydroconditioning. The data obtained were submitted to variance analysis, where the means were compared through the Tukey test to 5% probability and quantitative data analyzed by polynomial regression. Chia responded satisfactorily regarding vegetative development to the application of the dose of 250 g/pot of organic compound added to the growing substrate. At the time of planting, pot cultivation and the climatic conditions of The Brejo of Paraiba allowed an anticipation of the chia crop cycle for 87 days. The dose of 250 g also allowed germination of 80% of seeds from plants of this treatment. The seeds submitted to hydroconditioning showed a reduction in germination and vigor, in relation to seeds that were not hydroconditioned, i.e., although hydroconditioning anticipated the germination phases, it was not able to inhibit the toxic effects of NaCl, and this pre-germination treatment was not indicated for chia seeds.